Ultra-Wideband Temperature Dependent Dielectric Spectroscopy of Porcine Tissue and Blood in the Microwave Frequency Range - Ley, Sebastian; Schilling, Susanne; Fiser, Ondrej; Vrba, Jan; Sachs, Jürgen; Helbig, Marko (Sensors (Basel, Switzerland), 2019)
The knowledge of frequency and temperature dependent dielectric properties of tissue is essential to develop ultra-wideband diagnostic technologies, such as a non-invasive temperature monitoring system during hyperthermia treatment. To this end, we characterized the dielectric properties of animal liver, muscle, fat and blood in the microwave frequency range from 0.5 GHz to 7 GHz and in the temperature range between 30 °C and 50 °C. The measured data were modeled to a two-pole Cole-Cole model and a second-order polynomial was introduced to fit the Cole-Cole parameters as a function of temperature. The parametric model provides access to the dielectric properties of tissue at any frequency and temperature in the specified range.
Keywords: tuky; Muscles; játra; krev; Humans; M-sequence; Algorithms; Temperature; Microwaves; svaly; open-ended coaxial probe; teplota; impedanční spektroskopie; Models, Biological; Dielectric Spectroscopy; lidé; zvířata; Swine; dielectric spectroscopy; Liver; mikrovlny; biologické modely; algoritmy; ultra-wideband; Blood; Fats; Animals; elektrická impedance; Electric Impedance; temperature dependent dielectric properties of blood, fat, liver, muscle; prasata